Pengaruh Video Pembelajaran Berbasis Case Method Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas X SMK Adi Karya Ranah Pesisir - Asanah, Sahratun; Pratiwi, Rahmi (STKIP Pesisir Selatan, 2024)
This research is motivated by students' lack of understanding of Indonesian language learning materials, this is due to the media used by teachers in the learning process is still in the form of textbooks that do not illustrate learning materials. In an effort to improve student learning outcomes, the application of case method-based learning videos appears as an alternative that can solve these problems. This study aims to reveal the effect of case method-based learning videos on student learning outcomes in Indonesian language subjects in class X SMK Adi Karya Ranah Pesisir. This type of research is quantitative research with the form of quasi experiment. The population of this research is class X students of SMK Adi Karya Ranah Pesisir which amounted to 62 students. Data collection technique used test technique. From the research results obtained the average value of the experimental group of 80.403 is higher than the average value of the control group of 74.67. From the t test analysis obtained ????ℎ???????????????????? > ???????????????????????? = 2.99 > 2.00, meaning that there is a significant difference in the value of learning outcomes at the α 0.05 level. So it can be concluded that the use of learning video media has an effect on student learning outcomes in class X Indonesian language subjects at SMK Adi Karya Ranah Pesisir